Modelling and onsite testing on dynamic thermal responses of built environment in passive solar rooms on Tibetan plateau - Zhang, Yin; Han, Wenyang; Qi, Yicong (Frontiers in Energy Research, 2024)
Accurate prediction of indoor thermal environment and heating energy consumption is crucial to building energy efficiency. However, plateau areas have high altitude, low atmospheric pressure and intense solar radiation. Traditional thermal modelling methods are mainly based on more common and less elevated zones, regardless of the unique climatic features, resulting in disparities or errors in building load prediction and energy efficiency evaluation. In this paper, a novel dynamic building thermal model is proposed to accurately predict indoor thermal environment and heating consumption for passive buildings in high-altitude plateau regions. Moreover, a prototypical building and experiment system are established for onsite testing on the dynamic thermal responses. The validation results indicate acceptable accuracy by field measured data with coefficient of variation below 30%. Furthermore, the preliminary results also show that impact factors related to solar radiation, such as window-to-wall ratios, building orientations, and heat transfer coefficients, have more significant influence for heating energy consumption in plateau buildings. This work can provide methodological support for building thermal design and heating energy efficiency improvement for high altitude plateau areas.